Academic Exchanges between Brazil and China: The case of the Confucius Institutes in Brazil (Research, Society and Development, 2022)
We examine academic exchange between Brazil and China, specifically the case of the Confucius Institutes (CIs) in Brazil, through the experiences of UNESP and UNICAMP. The aim is to understand how the CIs contribute to academic exchange in the context of economic and cultural cooperation between Brazil and China. Bibliographic and bibliometric research was carried out, through a multi-method methodology, which unites quantitative and qualitative research. The justification is found in the political, cultural, and economic movements that foment Brazil-China relations through the BRICS. Brazil has twelve CIs and no one from them seeks to indoctrinate through Confucianism, rather their aim is to spread the Mandarin language.